2019
DOI: 10.1002/ece3.5106
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale genetic structure and flowering output of the seagrass Enhalus acoroides undergoing disturbance

Abstract: Seagrass are under great stress in the tropical coast of Asia, where Enhalus acoroides is frequently the dominant species with a large food web. Here, we investigate the question of the fine‐scale genetic structure of this ecologically important foundation species, subject to severe anthropogenic disturbance in China. The genetic structure will illuminate potential mechanisms for population dynamics and sustainability, which are critical for preservation of biodiversity and for decision‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Populations of E. acoroides in our study are sustained by clonal growth and local seed recruitment which confirms the mixed reproduction strategy in populations of Hainan Island affected by physical disturbance and catchment effluents ( Yu et al, 2019 ). Becheler et al (2014) studied temporal dynamics of clonal structure for Zostera marina and identified similar patterns of clonal richness and structure whereas populations persisted by both initial recruitment, with a stable core of clones which dominance increased over time, and repeated (annual) recruitment of seedlings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Populations of E. acoroides in our study are sustained by clonal growth and local seed recruitment which confirms the mixed reproduction strategy in populations of Hainan Island affected by physical disturbance and catchment effluents ( Yu et al, 2019 ). Becheler et al (2014) studied temporal dynamics of clonal structure for Zostera marina and identified similar patterns of clonal richness and structure whereas populations persisted by both initial recruitment, with a stable core of clones which dominance increased over time, and repeated (annual) recruitment of seedlings.…”
Section: Discussionsupporting
confidence: 83%
“…A higher relatedness of individuals over small distances within meadows (5–10 m) was found in more disturbed sites on both ramet level, due to the aggregation of clones over several meters, and genet level. The aggregated distribution of pollen in male floating flowers and of seeds that are released simultaneously from the floating fruit could explain the fine-scale genetic structure found for E. acoroides among genets rather than pollen and seed dispersal restriction ( Yu et al, 2019 ). The effect of the aggregated dispersal of propagules on the fine-scale structure may be elevated in disturbed sites when population density is low as a result of high mortality and decreased reproductive output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, E. acoroides is the dominant species along the east coastline of Hainan Island, of which the distribution area has been declining dramatically (Chen et al 2015). This dioecious seagrass displays the capacity for both sexual and clonal reproduction (den Hartog 1970;Yu et al 2019). Most of the seagrasses pollinate underwater mediated by water currents (Ackerman 2006).…”
Section: Enhalus Acoroides; Illumina Sequencing; Chloroplast Genome; mentioning
confidence: 99%
“…Observational surveys of clonal plants provide mixed evidence regarding the correlation between genotypic diversity and disturbance (e.g. McMahon et al., 2017; Reisch & Scheitler, 2009; Reynolds et al., 2019; Rusterholz et al., 2009; Yu et al., 2019), and disentangling the underlying mechanisms driving variance in this relationship remains an important avenue of research (Banks et al., 2013). Manipulative field experiments can assess the effects of varying disturbance regimes on the recruitment of new individuals (Herrera & Bazaga, 2016; Hidding et al., 2014; Macreadie et al., 2014; Peng et al., 2015; Reusch, 2006; Veeneklaas et al., 2011) but sampling at a fine enough scale to capture the effects of disturbance on altering the outcome of inter‐genotypic interactions is challenging.…”
Section: Introductionmentioning
confidence: 99%